2022
DOI: 10.22199/issn.0717-6279-4581
|View full text |Cite
|
Sign up to set email alerts
|

On the isotopic characterizations of generalized Bol loops

Abstract: In this study, the notion of isotopy of generalized Bol loop is characterized. A loop isotope of a σ-generalized Bol loop is shown to be a σ’-generalized Bol loop if σ’ fixes its (isotope) identity element where σ’ is some conjugate of σ. A loop isotope of a σ-generalized Bol loop is shown to be a σ’-generalized Bol loop if and only if the image of the isotope’s identity element under σ’ is right nuclear (where σ’ is some conjugate of σ). It is shown that a generalized Bol loop can be constructed using a group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In (Adeniran et al [2], 2015) carried out a study of some isotopic characterisation of generalised Bol loops. In (Jaiyéo .…”
Section: Middle Bol Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…In (Adeniran et al [2], 2015) carried out a study of some isotopic characterisation of generalised Bol loops. In (Jaiyéo .…”
Section: Middle Bol Loopmentioning
confidence: 99%
“…lá et al [18], 2017) studied the holomorphic structure of middle Bol loops and showed that the holomorph of a commutative loop is commutative middle Bol loop if and only if the loop is a middle Bol loop and its automorphism group is abelian. Adeniran et al [3,4], Jaiyéo . lá and Popoola [28] studied generalised Bol loops.…”
Section: Middle Bol Loopmentioning
confidence: 99%
“…In 2015, Adeniran et al [6] carried out a study of some isotopic characterisation of generalised Bol loops. In 2017, Jaiyéo .…”
Section: Introductionmentioning
confidence: 99%
“…lá et al [23] studied the holomorphic structure of middle Bol loops and showed that the holomorph of a commutative loop is a commutative middle Bol loop if and only if the loop is a middle Bol loop and its automorphism group is abelian. Adeniran et al [7,8], Jaiyéo . lá and Popoola [29] studied generalised Bol loops.…”
Section: Introductionmentioning
confidence: 99%